Thermodynamic modulation of folding and aggregation energy landscape by DNA binding of functional domains of TDP-43 - Patni, Divya; Jha, Santosh Kumar (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2023)
TDP-43 is a vital nucleic acid binding protein which forms stress-induced aberrant aggregates in around 97% cases of ALS, a fatal neurodegenerative disease. The functional tandem RRM domain of the protein (TDP-43tRRM) has been shown to undergo amyloid-like aggregation under stress in a pH-dependent fashion. However, the underlying thermodynamic and molecular basis of aggregation and how the energy landscape of folding, stability, and aggregation are coupled and modulated by nucleic acid binding is poorly understood. Here, we show that the pH stress thermodynamically destabilizes the native protein and systematically populates the unfoldedlike aggregation-prone molecules which leads to amyloid-like aggregation. We observed that specific DNA binding inhibits aggregation and populates native-like compact monomeric state even under low-pH stress as measured by circular dichroism, ANS binding, size exclusion chromatography, and transmission electron microscopy. We show that DNA-binding thermodynamically stabilizes and populates the native state even under stress and reduces the population of unfolded-like aggregation-prone molecules which leads to systematic aggregation inhibition. Our results suggest that thermodynamic modulation of the folding and aggregation energy landscape by nucleic-acid-like molecules could be a promising approach for effective therapeutic intervention in TDP-43-associated proteinopathies.
Keywords: Amyloid-like aggregation; Nucleic acid binding; RNA recognition motifs (RRMs); TDP-43; Thermodynamic stability